Cult books revisited: Gustavo Gutierrez's A Theology of Liberation. Issue 4 (August 2017) - Gorringe, Tim
Although nearly 50 years old, Gustavo Gutierrez's A Theology of Liberation remains a key text, especially in its challenge to the Church, its embrace of humane values and its call for a different world order.